1980
DOI: 10.1107/s0567739480000368
|View full text |Cite
|
Sign up to set email alerts
|

An improved method for the determination of microstructural parameters by diffraction-profile Fourier analysis

Abstract: The analysis of the influence of the background and truncation errors on the Fourier transform of the diffraction profile is extended with respect to the work that has already been done by others and a critical evaluation of the established Fourier methods for the determination of the microstructural parametersaverage dimensions of crystallites and paracrystalline microdomains, lattice-distortion parameters and cumulants of the strain distribution -is presented. It is shown that, contrary to the case of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…4.2). Zocchi [ 73 ] suggested that fitting the straight line through the first derivatives of the Fourier coefficients, instead of through the coefficients themselves, would solve the “hook”-effect problem.…”
Section: Previous Studiesmentioning
confidence: 99%
“…4.2). Zocchi [ 73 ] suggested that fitting the straight line through the first derivatives of the Fourier coefficients, instead of through the coefficients themselves, would solve the “hook”-effect problem.…”
Section: Previous Studiesmentioning
confidence: 99%
“…They almost certainly apply also to methods used when only a single order is visible. The separation of size and disorder from a single reflection (Mignot & Rondot, 1975;Zocchi, 1980;Nandi, Kuo, Schlosberg, Wissler, Cohen & Crist, 1984) depends entirely on the use of normalized coefficients of the orders which we have shown to be in serious error. Rational function extrapolation might still be valid, but the methods of testing this which we have described cannot be used when only one order of a reflection is available.…”
Section: Discussionmentioning
confidence: 88%
“…This method does not take into account the possible lattice distortions like paracrystalline disorder present in these starches. The inadequacies that exist in Scherrer's method have been pointed out by earlier investigators (Warren 1955(Warren , 1959Mignot and Rondot 1975;Zocchi 1980;Nandi et al 1984).…”
Section: Introductionmentioning
confidence: 98%